Pengembangan Modul Ajar Berbasis Experiential Learning pada Pembelajaran Termodinamika Teknik - Arif Susanto; Widiyatmoko, Widiyatmoko; Slamet Riyadi (Pusat Riset dan Inovasi Nasional, 2025)
The experiential learning model can provide opportunities for students to learn something based on their own experiences. This study aims to develop experiential learning model learning tools and performance assessment techniques in thermodynamics courses. The method applied in this study uses a mixed method with a 4D development model (Define, Design, Development, and Disseminate). The study was conducted in the Automotive Engineering Education Study Program, Muhammadiyah University of Purworejo with the research subjects being a class in semester III with a total of 30 students. Data collection techniques include device validation, practicality testing, device effectiveness, and documentation. Analysis of research data uses validity analysis, which is descriptive by outlining suggestions and input. The results of this study are producing learning module devices that are